Personal responsibility with health in Cuba: Mapping and play of actors for its promotion - Isabel Pilar Luis Gonzálvez; Yusdanys Torres Jiménez; Adolfo Gerardo Álvarez Pérez (Medisur)
Foundation: for any health goal to be achieved, it is necessary to involve multiple social actors whose intersectoral participation conditions the materialization of public health policies. Objective: provide the health sector with sufficient decision tools to implement a policy of intersectoral alliances to promote personal responsibility with the health of the Cuban population in a time horizon until 2030. Methods: strategic prospective study since January 2018 to March 2020. The Matrix of Alliances and Conflicts method was used: tactics, objectives, recommendations, with the participation of 12 experts. Results: 25 actors who formed 10 groups were identified. The actor with the greatest power are the citizens; Meanwhile, the strategic objective with the greatest mobilization is to transcend the paternalistic paradigm of health care practice in Cuba. The possibility of working intersectorally to develop lasting alliances between all the actors involved was demonstrated and that if there are contradictions these will not have an antagonistic nature. On the contrary, they can behave as elements that generate innovative solutions for future development. Conclusions: the mapping and analysis of the set of actors made it possible to demonstrate the possibilities of alliances between social actors and their strategic alignment with the formulated strategic objectives. It is recommended to monitor the evolution of this situation during the planned time horizon with the aim of reevaluating the system and reducing uncertainty in the face of a changing environment.